Inside Every Problem Lies an Opportunity: Senior Caregiver Perspectives - Truhlářová, Zuzana; Michek, Stanislav; Haviger, Jiří; Zajacová, Melanie; Havigerová, Jana Marie (Social Welfare: Interdisciplinary Approach, 2025)
This study examined the impact of the recent pandemic on 253 Czech social workers in senior residential care, focusing on their emotional states and problem-solving experiences. By using PHQ-9 and GAD-7, the research found that 35% of the respondents reported moderate to severe depression, and 27% admitted similar anxiety levels. Contrary to expectations, private context variables showed no significant correlation with these emotional states. However, corpus analysis identified distinct verbal expressions: loneliness, financial deterioration, and chaos in higher depression groups, and information management challenges in higher anxiety groups. The most frequent problems addressed were behavioral issues, motivation, and communication. A measurable connection existed between problem characteristics and emotional states, with higher depression linked to economic problems and strained non-work relationships, and higher anxiety associated with information management difficulties. Social workers adapted by increasing their IT use, reducing administrative tasks, and enhancing client communication. These outcomes highlight their resilience and capacity to manage stress positively during challenging times. Their crucial role in ensuring the dignified lives of seniors, combined with their adaptability and commitment, offers a promising outlook for their mental health and well-being when facing future challenges.
Keywords: social workers; older adults care; depression; anxiety; problems solved